The Speaking Disfluencies in the University Students’ Classroom Conversation - Siahaan, Sanggam; Situmeang, Siska; Siahaan, Fine Eirene (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The main topic as the research focus in this study deals with the investigation of the category of the speaking disfluencies of the students of the English Study Program. To explore the types of the speaking disfluency produced by the students of the English Study Program of FKIP Universitas HKBP Nommensen Pematangsiantar in their classroom conversationThe design of this research is categorized to a qualitative design. The technique of the data collection is by participant observation. By this technique the researcher functions as the key instrument in the data collection. In collecting the data the researcher is acting as a substitute lecturer giving a subject in Interpersonal Speaking The results of the study present an analysis of data on the types of speech impediments produced by students of the English Study Program at the University of HKBP Nommensen Pematangsiantar FKIP in their speeches in speaking class. And find analysis data on how each type of speech disfluency is used by students of the English Language Study Program at the HKBP Nommensen University FKIPThe students of English program FKIP Nommensen University use all of the type’s disfluency such as Filler or Repairs, Repetition, Hesitation and False Starts. They use Fillers or Repair while they are having a speech in front of their classroom and occurs every five to eight words.